2020
DOI: 10.1186/s13045-020-00942-x
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: m6A mRNA methylation initiated by METTL3 directly promotes YAP translation and increases YAP activity by regulating the MALAT1-miR-1914-3p-YAP axis to induce NSCLC drug resistance and metastasis

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Similar studies have yielded different results in different tumors. Similarly, high expression of METTL3, YTHDF3, and YTHDF1 induced NSCLC drug resistance and metastasis by promoting m6A methylation of YAP mRNA and translating [ 42 ]. Finally, the analysis of tumor stemness shows that the m6A protein-binding breast cancer samples have the strongest tumor stemness among the four subtypes, which is consistent with the previous analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have yielded different results in different tumors. Similarly, high expression of METTL3, YTHDF3, and YTHDF1 induced NSCLC drug resistance and metastasis by promoting m6A methylation of YAP mRNA and translating [ 42 ]. Finally, the analysis of tumor stemness shows that the m6A protein-binding breast cancer samples have the strongest tumor stemness among the four subtypes, which is consistent with the previous analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of studies have shown that changes in m6A affected tumor progression, including proliferation, growth, invasion, and metastasis ( 9 ). In addition, studies have shown that METTL3-mediated m6A mRNA methylation improved the stability of YAP mRNA by regulating the MALAT1-miR-1914-3p-YAP axis and increased the induction of NSCLC drug resistance and metastasis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in liver cancer, YTHDF2 modulated the m6A methylation of OCT4 mRNA and promoted the metastasis of liver cancer stem cells 54 . Furthermore, m6A modification in mRNA initiated by METTL3 directly promoted YAP translation and increased YAP activity by regulating the MALAT1-miR-1914-3p-YAP axis to induce NSCLC drug resistance and metastasis 55 . METTL3-mediated m6A modification was critical for EMT and metastasis of gastric cancer (GC).…”
Section: The Relationship Of M6a Modification and Cancer Stemnessmentioning
confidence: 99%